2020
DOI: 10.1177/2473011420914561
|View full text |Cite
|
Sign up to set email alerts
|

Knee Scooter–Related Injuries: A Survey of Foot and Ankle Orthopedic Surgeons

Abstract: Background: Knee scooters (“scooters”) are a commonly used device to facilitate postoperative adherence to weightbearing restrictions. Although high rates of falls have been reported, little is known about injuries related to scooter use. Methods: We analyzed survey responses from 316 of 2046 members (15%) of the American Orthopaedic Foot & Ankle Society in May-June 2019 describing (1) frequency of scooter recommendation; (2) indications for which they recommended scooters; (3) characteristics of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Moreover, obstacles such as stairs cannot be overcome without assistance. 5 , 12 , 16 , 26 An alternative that combines unloading without crutches and high mobility is an HFSO ( Figure 1 ) that promises higher patient satisfaction and comfort. 12 , 17 The mode of action of such an orthosis is based on the orthosis being applied with the knee bent at 90 degrees on the affected operated side.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, obstacles such as stairs cannot be overcome without assistance. 5 , 12 , 16 , 26 An alternative that combines unloading without crutches and high mobility is an HFSO ( Figure 1 ) that promises higher patient satisfaction and comfort. 12 , 17 The mode of action of such an orthosis is based on the orthosis being applied with the knee bent at 90 degrees on the affected operated side.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative falls may lead to complications such as fracture, revision surgeries, hospital readmissions, unnecessary emergency department visits, or health care provider evalautions. 53 , 73 , 102 The incidence of falls in the first year following discharge for total knee or hip arthroplasty has been reported to be as high as 43%. 50 A more recent study on foot and ankle surgery reported a 29% incidence of falls in the first 6 weeks after discharge.…”
Section: Presentation: Common Physical Impairments and Psychological ...mentioning
confidence: 99%
“… 108 In a survey of American Orthopaedic Foot & Ankle Society surgeons, the prevalence of postoperative knee scooter–related injuries was estimated to be 2.5%, and 34% of those injuries were treated operatively. 73 Despite the apparent risk associated with knee scooter use, patients report very high satisfaction scores and continue to prefer knee scooters over conventional ambulatory aids. 88 , 102 , 111 There have been no studies investigating the effect of preoperative physical therapy, ambulatory aid training, patient education or other preventative strategies on fall risk after foot and ankle surgery.…”
Section: Presentation: Common Physical Impairments and Psychological ...mentioning
confidence: 99%
“…41 Roughly 50% of the surgeons had prescribed an RKS with a mean reported complication rate of 2.5%. 41 This is substantially lower than the 43% fall rate cited by Yeoh et al 55 The high complication rate of 43% in the series by Yeoh et al may be attributable to 67% of their patients not receiving training or education on the RKS prior to use and the inherent reporting bias of survey studies. 55 Risk factors identified by Rahman et al 41 were female gender, age >44 years, obesity, and sedentary lifestyle.…”
Section: Rolling Knee Scootermentioning
confidence: 99%
“…They found that the majority of foot and ankle surgeons were using the RKS for patients who were made nonweightbearing after arthrodesis and fracture fixation. 41 Roughly 50% of the surgeons had prescribed an RKS with a mean reported complication rate of 2.5%. 41 This is substantially lower than the 43% fall rate cited by Yeoh et al 55 The high complication rate of 43% in the series by Yeoh et al may be attributable to 67% of their patients not receiving training or education on the RKS prior to use and the inherent reporting bias of survey studies.…”
Section: Novel Leadsmentioning
confidence: 99%